Pengaruh Pemberian Kompres Dingin Terhadap Penurunan Skala Nyeri Pemasangan Infus Pada Anak Usia Sekolah - Sri Enawati; Lathifah Rizky Nur Ramadhina; Nurul Istiqomah; Anik Enikmawati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Background : School-age children are very susceptible to diseases caused by environmental factors, hygiene, and unhealthy nutritional intake, so they are more likely to suffer from diseases (Wong, 2012). Children who must receive treatment in the hospital often gain experience from the various invasive procedures that need to be carried out. The infusion procedure is an invasive procedure that is often carried out when treating children in hospitals, this action is done by inserting a needle into the child's blood vessel which can cause pain (Hockenberry & Wilson, 2012). Infusion is the second source of pain felt by children after the disease they suffer (Indriyani, 2013).Objective : To determine the effect of cold compresses on decreasing the pain scale of infusion in children. Research Methods : The type of research used is quantitative research, namely research related to numbers, starting from data collection, interpretation of the data and the appearance of the results, while the design used in this study is a (quasi - experimental design). Results : The results obtained using the non-parametric test, it was found that the p value was 0.003. Because p value (0.003) < (0.05) then (Ha) is accepted. So it can be concluded that there is an effect of cold compresses on reducing the pain scale of infusion in school-age children. Conclusion : There is an effect of cold compresses on reducing the pain scale of infusion in school-age children.